2020
DOI: 10.1109/tpel.2020.2985117
|View full text |Cite
|
Sign up to set email alerts
|

Microchannel Thermal Management System With Two-Phase Flow for Power Electronics Over 500 W/cm2 Heat Dissipation

Abstract: In this paper, a microchannel thermal management system (MTMS) with the two-phase flow using the refrigerant R1234yf with low global warming potential is presented. The thermal test vehicles (TTVs) were made of either single or multiple thermal test chips embedded in the substrates, which were then attached to the MTMS. The system included two identical aluminum microchannel heat sinks (MHSs) connected in series in the cooling loop, which also consisted of a gas flowmeter, a miniature compressor, a condenser, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 30 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…An environment-friendly refrigerant with low boiling points, R1234yf, was selected as a working fluid. The experimental results showed that the TMS could dissipate a heat flux of 526 W/cm 2 while maintaining the junction temperature below 120 • C. Moreover, for SiC-based power electronics with a higher junction temperature, this system was expected to dissipate a heat flux up to 750 W/cm 2 [86]. Recently, T'Jollyn et al [90] experimentally investigated the heat transfer performance of the baseplate via pool boiling.…”
Section: Two-phase Baseplate Coolingmentioning
confidence: 99%
“…An environment-friendly refrigerant with low boiling points, R1234yf, was selected as a working fluid. The experimental results showed that the TMS could dissipate a heat flux of 526 W/cm 2 while maintaining the junction temperature below 120 • C. Moreover, for SiC-based power electronics with a higher junction temperature, this system was expected to dissipate a heat flux up to 750 W/cm 2 [86]. Recently, T'Jollyn et al [90] experimentally investigated the heat transfer performance of the baseplate via pool boiling.…”
Section: Two-phase Baseplate Coolingmentioning
confidence: 99%
“…However, the temperature gradient of pin-fin structures is higher than that of microchannels. A microchannel design provides a larger contact surface area and achieves better cooling for power modules [19][20][21]. In addition, a two-phase cooling scheme [22][23][24][25] can also be used to enhanced heat dissipation in power modules.…”
Section: Introductionmentioning
confidence: 99%